Use of Poly(vinyl alcohol) in Spray-Dried Dispersions: Enhancing Solubility and Stability of Proteolysis Targeting Chimeras - Lena Mareczek; Lena K. Mueller; Laura Halstenberg; Thomas M. Geiger; Michael Walz; Min Zheng; Felix Hausch (MDPI AG, 2024)
PROTACs, proteolysis targeting chimeras, are bifunctional molecules inducing protein degradation through a unique proximity-based mode of action. While offering several advantages unachievable by classical drugs, PROTACs have unfavorable physicochemical properties that pose challenges in application and formulation. In this study, we show the solubility enhancement of two PROTACs, ARV-110 and SelDeg51, using Poly(vinyl alcohol). Hereby, we apply a three-fluid nozzle spray drying set-up to generate an amorphous solid dispersion with a 30% w/w drug loading with the respective PROTACs and the hydrophilic polymer. Dissolution enhancement was achieved and demonstrated for t = 0 and t = 4 weeks at 5 °C using a phosphate buffer with a pH of 6.8. A pH shift study on ARV-110-PVA is shown, covering transfer from simulated gastric fluid (SGF) at pH 2.0 to fasted-state simulated intestinal fluid (FaSSIF) at pH 6.5. Additionally, activity studies and binding assays of the pure SelDeg51 versus the spray-dried SelDeg51-PVA indicate no difference between both samples. Our results show how modern enabling formulation technologies can partially alleviate challenging physicochemical properties, such as the poor solubility of increasingly large 'small' molecules.